REPRESENTATION OF THE CHARACTER CONCEPT "ENGLISHMAN" IN THE NOVEL BY J. ALDRIDGE "DIPLOMAT" - Sabina Avazjonovna Makhmudova (Journals Park Publishing, 2023)
The article substantiates the understanding of the artistic concept as a "microsystem" in various situations of the novel "The Diplomat". The character concept of "Englishman" has a wide semantic palette and various types of representation, reflecting the author's modality.
Keywords: concept, character concept, professional deformation, linguo-stylistic self-characterization.